How to cross the line: design principles for interdisciplinary education [version 2; peer review: 2 approved, 2 not approved] - Enny Das; Jessica Oudenampsen; Marjolein van de Pol; Nicole Blijlevens (MedEdPublish)
Background Interdisciplinary learning is gaining popularity in higher education worldwide. Currently, knowledge about how to appropriately design interdisciplinary education is still lacking. The current study presents the iterative development, pilot, and implementation of an interdisciplinary course in healthcare communication. Methods We used a design-based educational research approach in four phases to construct the program. In phase 1, we conducted a narrative review of the literature and distilled several prerequisites for interdisciplinary learning. In phase 2, we implemented two pilot courses with a focus on the content and the interdisciplinary context of the course. In research phase 3, we implemented the course during three consecutive years, with yearly evaluations of the course. In phase 4, we distilled design principles based on evaluation and reflection of the previous research phases. Results We elaborate on the various components of the design itself. Furthermore, using data from surveys, panel discussions and interviews, we reflect on the content and outcomes of the interdisciplinary course. We propose seven evidence-informed ‘crossing the line’ design principles for future interdisciplinary education. Conclusions The developed design principles pertain to interdisciplinary education in general and transcend subject-specific boundaries. The design principles are applicable in a wide range of higher education disciplines.